2016
DOI: 10.1063/1.4941332
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of energy exchange between inter- and intramolecular degrees of freedom in crystalline 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) with implications for coarse-grained simulations of shock waves in polyatomic molecular crystals

Abstract: In this report, we characterize the kinetics and dynamics of energy exchange between intramolecular and intermolecular degrees of freedom (DoF) in crystalline 1,3,5-triamino-2,4,6-trinitrobenzene (TATB). All-atom molecular dynamics (MD) simulations are used to obtain predictions for relaxation from certain limiting initial distributions of energy between the intra- and intermolecular DoF. The results are used to parameterize a coarse-grained Dissipative Particle Dynamics at constant Energy (DPDE) model for TAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Based on a quantum chemistry calculation of the vibrational frequencies for an isolated TATB molecule, Kroonblawd et al . calculated the temperature dependence of the specific heat per molecule, neglecting the three‐apiece local translations and rotations of/about the molecular center of mass at a lattice site, and modeled it as a sum to two Einstein oscillators. Under the reasonable assumption that these six ‘external oscillators’ in the crystal would be classically populated ( i. e ., in the high‐temperature limit of quantum mechanics) even at very low temperatures, the final form used here for the temperature‐dependent specific heat of the crystal is: trueCv()T=A1()θ1normalT2e-θ1normalTnormale-θ1T-12+A2()θ2normalT2e-θ2normalTnormale-θ2T-12+B …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a quantum chemistry calculation of the vibrational frequencies for an isolated TATB molecule, Kroonblawd et al . calculated the temperature dependence of the specific heat per molecule, neglecting the three‐apiece local translations and rotations of/about the molecular center of mass at a lattice site, and modeled it as a sum to two Einstein oscillators. Under the reasonable assumption that these six ‘external oscillators’ in the crystal would be classically populated ( i. e ., in the high‐temperature limit of quantum mechanics) even at very low temperatures, the final form used here for the temperature‐dependent specific heat of the crystal is: trueCv()T=A1()θ1normalT2e-θ1normalTnormale-θ1T-12+A2()θ2normalT2e-θ2normalTnormale-θ2T-12+B …”
Section: Methodsmentioning
confidence: 99%
“…The crystal is triclinic with two molecules per unit cell. The structure of the crystal is strongly anisotropic and this is reflected in pronounced anisotropy for many of the thermal [39][40][41][42][43][44][45][46][47][48][49][50], mechanical [51][52][53][54][55][56][57][58][59][60], and optical properties [61].…”
Section: Introductionmentioning
confidence: 99%
“…TATB crystals tacking-fault energiesw ere also determined [25] using the HB-FF;t he exceptionally low barrier to slid-ing of the planar molecularl ayers was associated [7] with the formation of subtle dynamic structural transitions at (300 K, 0.0 GPa). Simulations of velocityp erturbation relaxation based on the HB-FF werer ecently used to calibrate the dissipative and stochastic parameters in am esoscale rigid-molecule dissipativep article dynamics (DPD) model for TATB [17].…”
Section: Tatb Force Fieldsmentioning
confidence: 99%
“…
1IntroductionCharacterizationo fe nergy transport processes in molecular materials usinga ll-atom molecular dynamics( MD) simulations provides anecessaryand physical basis for the prediction and understanding of experimentally undetermined properties [1][2][3][4][5][6][7],m any of whicha re needed for the parameterization of the kinds of continuum-based mesoscale engineeringm odels widely used to simulate energetic materials [8][9][10][11][12][13][14][15]. Accurate predictionsf or anisotropic bulk material properties such as the thermal conductivity and rate coefficientsf or energyt ransfer processes are necessary if parameterized models are to yield reliable predictions for dynamic processes such as shock loading [9][10][11][12][14][15][16][17][18],h ot spot formation and relaxation [9-12, 14, 15, 19],a nd initiation of chemistry [11,14,19].R ecentM D-based predictions for the thermal conductivity of the insensitivem olecular crystalline explosive 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) revealed significanta nisotropy for energy transport at T = 300 Ka nd P = 0.0 GPa [6,7]. ( Here and for all subsequent instances, pressures reported as 0.0 GPa formally correspond to 1atm, which is 0.0 GPa within the precision of our calculations.)
…”
mentioning
confidence: 99%
“…For these reasons, the numerical modeling of TATB crystal plays an essential part in studying its macroscopic behavior. For example, Mathew et al 6 and Kroonblawd et al 7 studied through molecular dynamics (MD) simulations its elastic− plastic response under displacement-controlled nanoindenta- tions and under shock. They reported that some studies 8 have suggested the existence of high defect density in grown crystals of TATB and subtle structural phase transitions under hydrostatic compression.…”
Section: Introductionmentioning
confidence: 99%